Health Narratives in the Greek Translated Press - Kaniklidou, Themis Panagiotis (Brazilian journalism research, 2016)
This paper looks see how meaning is constructed in translated news texts about health and science and awards a narrative potential to unforced translation shifts, moving along the theoretical lines of Baker’s Narrative Theory (2006). The thematic thread of health zooms in on “emotional frames” (Nabi, 2003) of risk and fear of human health that is narrated as being ’under attack’ by potentially dangerous diseases. Themes also orbit around schemas that promote hope and optimism about science represented as coming to the rescue of man from fear of the disease. The data consists of 21 pairs of English-Greek health news articles culled from the Greek newspapers I Kathimerini, To Vima and Ta Nea. Findings point towards translation as a process that employs lexicogrammatical and intrasentential configurations to a) give emphasis to the risk or hope dimensions underlying a heath or science story, b) enable the reflection or emergence of a cascade of public, conceptual and master narratives.